"It’s the workload, not the pictures that keep me up at night.": experiences of Norwegian police prosecutors working with child abuse cases - Rostad, Ingrid Steen (International journal of law, crime and justice, 2025)
Prosecutors are regularly exposed to traumatic accounts of crimes against children in their work. Accompanied by other stressors such as heavy caseloads and short deadlines, prosecutors in child abuse cases are at risk for psychological ill-health. We aimed to explore the experiences of prosecutors working as leading interrogators in cases of child abuse and to identify their most salient challenges and resources. We conducted semi-structured interviews with six prosecutors working in a police district in Norway, all specialized in child abuse cases. A thematic analysis identified the workload and being responsible for the investigation but without any authority to allocate resources as the main stressors. Further, the nature of the cases increases the stress, and the prosecutors are left out of debriefing routines. Further, they experience marginal acknowledgment and understanding from the management, and collegial support is scarce. The prosecutors describe the complexity and challenging part of investigating child abuse cases as highly motivating and meaningful.